ENERGY CONSUMPTION-OUTWARD FOREIGN DIRECT INVESTMENT-NATURAL RESOURCE RENTS NEXUS: EVIDENCE FROM BRICS-T COUNTRIES - Mumcu, Suat; İnce, Hüseyin (Suat TEKER, 2024)
Purpose- This research measures the impacts of population, economic development, outward foreign direct investment, and natural resource rent on energy consumption in BRICS-T countries (Brazil, Russia, India, China, South Africa and Turkey). The main objective of the study is to evaluate the impact of outward foreign direct investment and natural resource rents on environmental sustainability together and to examine the structure of the relationship between economic growth and energy consumption with the Environmentally Kuznet Curve (EKC) hypothesis. Methodology- This analysis, which was carried out within the framework of the STIRPAT (Stochastic Impacts by Regression on Population, Affluence, and Technology) theoretical model, examined the effects of factors on energy consumption with Driscoll-Kraay standard error fixed effects estimator as a result of the determination of country heterogeneity and robustness tests. Findings- The analyses show that population and gross domestic product per capita are positively related to energy consumption. At the same time, outward foreign direct investment decreases energy consumption in BRICS-T countries through the reverse spillover effect. The findings on the positive relationship between natural resource rents and energy consumption indicate that energy consumption increases in BRICS-T countries through fossil fuel-intensive production processes. The study also found a statistically significant inverted u-shaped curve between energy consumption and economic growth, but detecting a turning point outside the data set suggests that the EKC hypothesis is not valid in BRICS-T countries. Conclusion- The findings of the study show that outward foreign direct investment makes possible the transfer of environmentally friendly technologies from host countries to the home country and increases energy efficiency in the production process. Therefore, BRICS-T countries need to see outward foreign direct investment not only as an economic gain but also as a tool for environmental improvement. The fact that natural resource rents encourage fossil fuel dependency suggests that some of these resources should be directed to renewable energy projects. In conclusion, it is recommended that BRICS-T countries adopt green growth strategies, gradually remove fossil fuel subsidies and implement environmental regulations such as carbon tax to achieve sustainable development goals.
Keywords: Labor Economics; Çalışma Ekonomisi; Microeconomics (Other); Mikro İktisat (Diğer); Finance; Finans; Finance and Investment (Other); Finans ve Yatırım (Diğer); Business Administration; İşletme